A P wave‐based, on‐site method for earthquake early warning. Issue 5 (13th March 2015) - Colombelli, S.; Caruso, A.; Zollo, A.; Festa, G.; Kanamori, H.
Abstract: A new strategy for a P wave‐based, on‐site earthquake early warning system has been developed and tested on Japanese strong motion data. The key elements are the real‐time, continuous measurement of three peak amplitude parameters and their empirical combination to predict the ensuing peak ground velocity. The observed parameters are compared to threshold values and converted into a single, dimensionless variable. A local alert level is issued as soon as the empirical combination exceeds a given threshold. The performance of the method has been evaluated by applying the approach to the catalog of Japanese earthquake records and counting the relative percentage of successful, missed, and false alarms. We show that the joint use of three peak amplitude parameters improves the performance of the system as compared to the use of a single parameter, with a relative increase of successful alarms of about 35%. The proposed methodology provides a more reliable prediction of the expected ground shaking and improves the robustness of a single‐station, threshold‐based earthquake early warning system. Key Points: A P wave‐based method for an on‐site earthquake early warning system is proposed Three parameters are jointly used for the ground shaking prediction The combination of three parameters improves the robustness of the system